INTEGRATING MOODLE-BASED OF COMMUNICATIVE LANGUAGE TEACHING IN HIGHER EDUCATION - Prasetya, Rizky Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Inability to adapt and adjust in Moodle-based English teaching, especially communicative language teaching. This study aims to analyze the Communicative Language teaching approach used in Moodle-based English teaching in universities. The research design used is a qualitative approach with a sequential experimental research design and using semi-structured interviews. The research subjects were 12 English lecturers. The study results indicate that the process-based approach to communicative language learning adapts and adapts Moodle-based English teaching. Practices related to the knowledge and experience of lecturers in teaching English at Moodle. The study concludes that the pedagogical Moodle-based communicative language teaching approach should be improved, and the system provides tremendous possibilities. Moodle makes adjustments in its English pedagogical approach and sequentially develops teaching and learning productivity. The implication of the research is to make adjustments in the pedagogical approach of English and develop learning productivity by integrating it into computers and the Internet.